Food Processing - Alina Marc, Romina; Valero Díaz, Antonio; Denisse Posada Izquierdo, Guiomar (IntechOpen, 2020)
In view of the continuous evolution that is taking place in the field of food processing, this book aims to devise the most comprehensive presentation of up-to-date information in the specialized literature to improve existing knowledge. The chapters in this book have been divided into four sections. Section 1-Food Technologies in Food Processing-presents current technological processes used in food processing. Section 2-Quality of Raw Materials in Food Processing-presents the importance of the quality of raw materials used in food processing. Section 3-Treatments Used in Food Processing-presents the latest trends in treatments used in food processing. Section 4-Factors That Influence Food Processing-presents current information on the factors that influence food processing from the raw material to the packaging used.